"Slime" contact dermatitis: Case report and review of relevant allergens. Issue 3 (13th March 2019) - Anderson, L. Elizabeth; Treat, James R.; Brod, Bruce A.; Yu, JiaDe
Abstract: Homemade "slime" is currently a popular childhood hobby that can cause allergic and irritant contact dermatitis. We describe a case of hand dermatitis due to homemade "slime" with a positive patch test to methylchloroisothiazolinone (MCI)/methylisothiazolinone (MI) and MI. The most common potential allergens in "slime" collected from a review of "slime" recipes found on the Internet are reviewed. Abstract : Linked Content This article is linked to Jacob paper. To view this article visithttps://doi.org/10.1111/pde.13810 .